Trade Complementarity of India and China with Their Trading Partners in Silk Goods - P., Kumaresan (Prabandhan: Indian Journal of Management, 2011)
Silk is one of the oldest fibres known to man and remains as the most loved fibre, the world over. Though silk is a high value textile and consumed more by higher strata of the society, sericulture industry plays an important role in economic development of a country because of highly employment oriented, low capital intensive and remunerative nature of its production. India is the second largest producer of silk next only to China and the exports earning from Indian silk goods have significantly increased over the years. The complementarity in trade between the partners is essential for the growth of the trade between the countries. Therefore, the trade complementarity of India and China with their partners in the trade of silk goods is analyzed in the current study to understand the prospects of the expansion of trade in silk goods among these countries. The high values of complementarity index for both India and China indicate that all the major importing countries of silk goods maintained high level of complementarity with China and India in the trade in silk goods. However, China has maintained a higher level of complementarity in the trade of silk goods with its partner than that of India.